Design, fabrication and measurement of metal-semiconductor field effect transistor based on zinc oxide material - Tun, Hla Myo; Wulansari, Rizky Ema; Pradhan, Devasis; Naing, Zaw Min (Journal of Engineering Researcher and Lecturer, 2023)
The paper mainly focuses on the design, fabrication and measurement on Zinc Oxide (ZnO)-based Metal-Semiconductor Field Effect Transistor. The research problem in this study is difficulty on observing the electronic properties of ZnO materials to fabricate the high performance transistor design with non-toxic semiconductor materials. Even though the wide band gap materials of Group III and V possess high performance properties for fabricating the power electronics devices, the harmful impacts could not be reduced. The research solution for the problem statement in this study is emphasized on the non-toxic materials of Group II and VI-based high performance power electronics devices fabrication. The experimental studies of the device fabrication were conducted by Pulse Laser Deposition (PLD) process in standard laboratory. The step-by-step procedures for MSFET device fabrication were discussed and the confirmation of developed device fabrication was completed. The approaches on all measurement were completed based on band diagram condition, quantum interference on metal-semiconductor materials, and current-voltage characteristics. The step by step measurement for fabricated device for the proposed structure could be confirmed by standard measurement techniques. The proposed design has been validated for the utilization of high performance applications. The physical properties and physical characteristics for measurement results were confirmed by the theoretical analyses. The numerical analyses have been completed with the help of MATLAB. All results have been proved by recent research works.